Studies on the optical fluxes attenuation process in optoelectronic systems - Strelkova, T.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
In this paper, the statistical characteristics of output signals in optoelectronic
systems with a limited dynamic range are considered. The experimental results
concerning noises probability densities are adduced. It has been shown that the law of
output signal distribution depends on attenuation factor of neutral filter used for matching
the dynamic range. The output signal distribution law is well approximated by the steady
distributions with characterization index 0 < α < 2. Using the stable law as a limiting one
allows to avoid the contradiction between experimental data and common mathematical
models of signals based on the Poisson and Gaussian statistics and to reduce weak
signals detection errors in optoelectronic systems with implementation of neutral filters
for matching the dynamic range.